Laser Scissors and Tweezers to Study Chromosomes: A Review - Berns, Michael W. (Frontiers in Bioengineering and Biotechnology, 2020)
Starting in 1969 laser scissors have been used to study and manipulate chromosomes in mitotic animal cells. With the advent of optical tweezers in 1987, laser tweezers have been used to study the behavior and forces on chromosomes in mitotic and meiotic cells. The combination of laser scissors and tweezers were employed since 1991 to study various aspects of chromosome behavior during cell division and in 2018 to cut, move, and fuse chromosome fragments.